Draft memorandum on the place of nursing in a national health service - Nursing Times
1944-11-11 1944 1940s 4 pages 4 with so-called "private" nurses is strongly deprecated and should cease. 6. Industrial Nursing. — Industrial medicine is not included in the national scheme on the grounds that it lies outside the direct service for personal health. The Royal College of Nursing considers this a grave weakness, and emphasises that all types of medical and health service should be included. In its opinion, responsibility for the health services for workers during working hours should rest with the Ministry of Health, but the administration of the service should be the responsibility of the Ministry of Labour and National Service. Industrial Health Committees should be set up within the Central and Local Health Services Councils, with nursing representation, so as to co-ordinate and develop this branch of the service. Examination for Employment The medical examination of juveniles for employment might well be carried out at the health centre, where there will be access to past medical records. It might also be advisable to centralize all medical examinations for employment there. At present a worker with some disability may be examined at one factory after another with no guarantee that steps will be taken to correct the condition. This is not only wasteful of effort, but unconstructive ; co-ordination at the health centre should obviate it. Standardized health records, to be retained by each worker, like the war-time identity card, would facilitate employment under the more mobile conditions of labour envisaged in the future. At present the industrial health service available to many categories of workers is inadequate, notably with regard to workers engaged in commerce, the catering trades, building, agriculture, shipbuilding and in Government Departments. Mobile Units In cases where the factories are too small and scattered to command regular industrial medical services, health service facilities might be brought to the workers by means of a mobile unit maintained by the local health centre. Each centre serving an industrial district should include, on its staff, a nurse trained and experienced in industrial nursing, and well acquainted with the various types of employment and conditions of work in the neighbourhood. Industrial nurses will also be concerned with the rehabilitation and resettlement of workers. 7. Care of the Aged.— No health plan will be complete unless there is suitable accommodation for the care of those aged persons who, unaided, cannot entirely look after themselves, or for whom there is no adequate provision with relatives or friends. Plans are under discussion for the grouped housing of these old people in homely surroundings which will ensure them the maximum of independence while at the same time catering for their basic needs. The Royal College of Nursing considers that the experienced State-registered nurse has a leading part to play in the organization and administration of these communities and in the personal day-to-day supervision and care which will be required. SECTION IV : QUESTIONS TO THE MINISTER 1. Now that the White Paper on Social Security has been published, does the Minister of Health intend to submit further proposals on the development of social and preventive medicine? 2. Will the Minister give an assurance that, in the reorganization of the hospital services, care will be taken to safeguard the training of nurses? 3. Will the Minister implement the recommendation of the Athlone Committee that grants be given from national funds to all recognised training hospitals in respect of the national work done in the training of nurses? 4. Although the Minister states that, pending the result of certain inquiries, the inclusion of the mental health services in the National Health Plan would present difficulties, would he not consider preliminary steps at the present stage to secure the closer integration of the mental and physical health services? 292/847/3/96